Pengetahuan dan Perilaku Masyarakat Batu Bara tentang Pencegahan Covid-19 - Tya Mai Lina; Eliska Eliska (Pustaka Kesehatan, 2023)
Coronaviruses can cause disease in humans and animals including covid-19, that can spread through droplets from the nose or mouth when coughing or sneezing. Therefore, knowledge and good community behaviour are needed in preventing Covid-19. The purpose of the study was to describe the knowledge and behavior of the Batu Bara community in preventing Covid-19. The research was carried out in August 2020 using an online platform in Batu Bara community. This is a quantitative descriptive method, with a cross sectional research design. The population is residents who live in Batu Bara. As many as 30 respondents were obtained by accidental sampling technique. It was found that the respondent's knowledge were 3 respondents (10%) had poor knowledge in preventing Covid-19. Meanwhile, 29 respondents (96.6%) used masks and hand sanitizers. 26 respondents (86.6%) used antibiotics and 27 respondents (90%) had controlling the environment using disinfectants to prevent Covid-19. Eventhough the covid19 case in Batu Bara was 0%, they still adhered to health protocols and used masks when going out. Good personal healthy life always takes precautions to be free from transmission of the Covid-19 virus, and those who have not behaved according to the recommendations of the Ministry of Health in preventing Covid-19 should improve their behavior in order to suppress the spread of Covid-19 disease